Teaching Strategies to Promote Self-Reflection of Pedagogical Praxis in Teacher Training Processes - Isabel Badilla Zamora; Anthia Ramírez García; Laura Rizo Cuadra; Kattia Rojas Acevedo (Universidad Nacional, Costa Rica, 2014)
As part of a reflection process by the academic staff of the Basic Education Division (DEB) on the conceptualization and implementation of the praxis processes in the DEB student community, the research project entitled "Professional Praxis of Practice Teachers and Senior Teachers" was created in 2013.  The main objective of this project is to provide spaces to reflect and/or take action on the practice teaching of the participants involved in the DEB academic programs through action-research processes aimed at strengthening pedagogical praxis.  In addition, results obtained are shared by the academic team in order to know the reflections made by the students of the four DEB academic programs during their supervised practice teaching, and to identify the most significant aspects experienced during such practice teaching.  A teaching unit was designed to collect and reflect on aspects regarding their practicum experiences in elementary schools.  Finally, thanks to the project there was consistency between the theory students receive in classes and the practical-pedagogical axis in the curricula of the DEB academic programs, based on the practice teaching conducted by the student community.